Association between prolonged maternal smokeless tobacco use and pregnancy outcome - Rahman, ME; Hossain, MM; Rahman, AKMM; Das, SR (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13247 J. Dhaka Med. Coll. 2012; 21(1): 109-115